The Importance of Learning English as a Foreign Language Nowadays (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The significance of English in today's global society cannot be understated or disregarded because it is the most widely used language on earth. It takes perseverance and consistent practice to learn English. Students often have the mindset that it is impossible to become fluent in or proficient in the English language. Students that have this propensity are unable to learn English. Since the majority of students approach English learning from an exam perspective, they are unable to generate even a single sentence free of grammatical errors. Additionally, kids do not receive enough practice in order to acquire a language. If someone wishes to advance in their career, they must be literate in English. It is the principal window of the contemporary era.